New inverting modified CUK converter configurations with switched inductor (MCCSI) for high-voltage/low-current renewable applications - Maroti, Pandav Kiran; Padmanaban, Sanjeevikumar; Bhaskar, Mahajan Sagar; Blaabjerg, Frede; Wheeler, Patrick (2018)
Inverting Modified CUK Converter with Switched Inductor (MCCSI) configurations are articulated in the paper for high-voltage and low-current renewable energy applications. Based on the Switched Inductor (SI) position in MCC converter, four new modified CUK converter configurations are proposed as MCCSI-XLL, MCCSI-LYL, MCCSI-LLZ and MCCSI-XYZ. The mathematical analysis and comparison is shown in terms of the voltage conversion ratio, number of active and reactive components. The mode of operation of MCCSI-XLL configuration is discussed to understand the working concept of MCCSI configurations. The striking features of the proposed configurations are discussed in details. Operation of the proposed converter is verified by simulation in MatLab R2016a.